The Factors Related to the Interest of Women Chiildbearing Age (WUS) in Acetic Acid Visual Inspection (IVA) Screening in the Service Area of Puskesmas Gumelar Indonesia - Pratiwi, Hesti Intan; Susilo, Rakhmat; Purwito, Dedy; Handayani, Diyah Yulistika (UM Purwokerto Press, 2025)
Cervical cancer is the fourth leading cause of cancer death worldwide. In Indonesia, it is estimated that 41 new cases of cervical cancer occur every day, and approximately 20 people die daily from the disease. Puskesmas (Community Healthcare Center) Gumelar has the lowest IVA screening rate in the Banyumas Regency, at 2.7%. To identify the factors related to the interest of women of childbearing age (WUS) in undergoing Acetic Acid Visual Inspection (IVA) screening in the service area of Pukesmas Gumelar. Method: This quantitative correlational study used a cross-sectional design. Where the independent variables (knowledge, attitudes, access to information, role of health cadres, and family support) and dependent variable (interest) are measured or collected simultaneously at one point in time. The instrument used was a questionnaire. The respondents were 90 women of childbearing age from five villages in the Gumelar district. This research uses qualitative data analysis and sampling techniques using probability sampling with proportionate random sampling technique. The factor most associated with interest in VIA examination is knowledge (p-value 0.001) followed by access to information (p-value 0.003), attitude (p-value 0.005), family support (p-value 0.006) and the unrelated factor is the role of health cadres (p-value 0.064). Factors such as knowledge, attitude, access to information, and family support are related to the low interest of women of childbearing age in undergoing IVA screening.